Analysis of swimming individual anaerobic threshold and stroking parameters in triathlon. A case study - Ribeiro, J.; Santos, I.; Figueiredo, P.; Morais, P.; Colaco, P.; Fernandes, R. (Archivos de medicina del deporte, 2008)
Economy of locomotion in swimming, cycling and running is very well related to performance in triathlon. Reporting specifically to the anaerobic threshold, Sleivert and Rowlands (1996) stated that this physiological parameter is determinant to a high level triathlon performance when assessed in the appropriate exercise mode. In this sense, triathletes could make large improvements if they develop the above referred parameters. Additionally, in swimming, the ratio between the general biomechanical parameters, stroke rate (SR) and stroke lenght (SL), is assumed has a valid indicator of stroke efficiency. The purpose of this study was to assess the individual anaerobic threshold (In-dAnT), as well as to observe the kinetics of the stroking parameters, throughout an intermittent incremental front crawl swimming test. A triathlete (age: 17 years old; weight: 67 kg and height: 175 cm) of the National Portuguese Junior Team, performed a front crawl intermittent incremental protocol of 6 x 200 m with increments of 0.05 m/s per each stage (30 s rest intervals), being the initial velocity established according to the swimmer individual performance of the moment. Swimming velocity was controlled using a visual pacer (TAR.1.1, GBK-electronics, Portugal) with flashing lights in the bottom of the pool. Capillary blood samples for blood lactate concentration ([La ) analysis were collected from the earlobe at rest, after each stage and at the end of the experimental protocol (Lactate Pro auto-analyser). These [La ] allowed assessing IndAnT, which was determined by [La]/v curve modelling method (Machado, et al., 2006). SR was assessed trough a chronofrequencemeter and SL was calculated by the ratio between v and SR. The IndAnT occurred at a velocity of 1.32 m/s, which corresponds to 0.90 mmol.l -1 of [La]. This [La] value seems to be lower than those reported in the literature for swimmers, which are between 1.5 and 4.5 mmol.l -1 (cf. Fernandes, et al., 2005). This difference seems to be explained by the higher aerobic capacity of triathletes induced by mainly aerobic training regimens. This fact limits the use of the traditional 4 mmol.l -1 [La] as a reference value to assess IndAnT. It was also observed, as expected, a SR increase and a SL decreased during the incremental protocol, as well as a high positive correlation between SR and v (0.99, p<0.05). We conclude that triathlon has great specificity and that more accurate, specific and individualized testing protocols are needed in order to obtain more precise and objective results helping coaches on their daily training programs